Deliberasi Bagi Pembentukan Identitas Organisasi Keagamaan dan Budaya dalam Pengurangan Resiko Bencana Berbasis Komunitas (PRBK) - Abdul Jalil (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Back-grounded with problems the need of community participation, complex Disaster Risk Reduction program serves as among other action on the practice of deliberative approach as the right of a religious organization and culture at the local level that have been instituted and formed their organization, as well as the exploration of the results of the collaborative dialogue of their existence in the process of building an understanding of the importance of management issues. The object of study is Mulyodadi village because it includes areas that have the potential disaster, such as earthquakes, floods, and droughts. This paper aims to determine the deliberative practices in identity formation of civil society organizations. It deals with a programmatic framework for Disaster Risk Reduction in Indonesia, particularly studied in religious organizations particularly/culture at the grassroots level in Mulyodadi. The method of the research is participant observation, namely a visit and stay with the community as well as data collecting on the actors and organizations associated with religious/cultural and other forms of organized activities. Both religion and culture serve as the spirit and the driving motivation and action in a variety of disaster recovery. Religion has a divine moral values, and cultural values that have been established by the community. It includes institutionalization of the actors with a vehicle for achieving the organization's vision and mission and through the program, budget and human resources that are able to adapt and manage the external environment. The successful organization of resources and capital can form identity of both organizations.